Comprehensive Analysis of the Prognostic Role and Mutational Characteristics of m6A-Related Genes in Lung Squamous Cell Carcinoma - Gu, Chang; Shi, Xin; Qiu, Wenli; Huang, Zhenyu; Yu, Yan; Shen, Feng; Chen, Yumei; Pan, Xufeng (Frontiers in Cell and Developmental Biology, 2021)
Background: There has limited treatment therapies for lung squamous cell carcinoma (LUSC). M6A related genes may be the next therapeutic targets for LUSC. In this study, we explored the prognostic role and mutational characteristics of m6A related genes in LUSC. Methods: LUSC gene expression data, mutational data and corresponding clinical information were extracted from The Cancer Genome Atlas database. Differentially expressed genes (DEGs) were identified and the mutation characteristics of LUSC patients were explored. Then, m6A related genes were extracted and the correlations among the genes were detected. Finally, the prognostic role of the genes were investigated and nomogram model was developed. Besides, the protein-protein interaction (PPI) network was used to explore the potential interactions among the genes. Results: In total, there are 551 LUSC samples were enrolled in our study, containing 502 LUSC tumor samples and 49 adjacent normal LUSC samples, respectively. There were 2970 up-regulated DEGs and 1806 down-regulated DEGs were further explored. IGF2BP1 and RBM15 had significant co-occurrence frequency (p <0.05). Besides, METTL14 and ZC3H13 or YTHDF3 also had significant co-occurrence frequency (p <0.05). All the m6A related genes represent the positive correlation. WTAP was identified as a prognostic gene in TCGA database while YTHDC1 and YTHDF1 were identified as prognostic genes. In multivariate Cox analysis, YTHDF1, age, pN stage, pTNM stage and smoking were all identified as significant prognostic factors for OS. Conclusions: We investigated the expression patterns and mutational characteristics of LUSC patients and identified three potential independent prognostic m6A related genes (WTAP, YTHDC1 and YTHDF1) for OS in LUSC patients